FROM IMPORTED THEORY TO LOCAL PRACTICE: A QUALITATIVE STUDY OF PEDAGOGICAL TRANSLATION IN EAST AFRICA - Ruhangisa, Valentine (IAI Sunan Giri Trenggalek, 2026)
This research explores the translation of imported teaching theories into practice by secondary school teachers in Kenya, Tanzania and Uganda. The focus of the problem is the disconnect between global teaching theories and practices in East Africa. Despite ongoing promotion of learner-centered, competency-based and constructivist pedagogies by governments and international entities, teaching practices have not changed or have only changed partially. This research aims to unravel the meanings, interpretations, resistance and transformations teachers make to imported teaching theories in their sociocultural and institutional contexts. This study used a qualitative comparative study design, with 72 teachers in 24 secondary schools. Semi-structured interviews, classroom observations and documents were analysed. The study shows that teachers engage in pedagogical translation in the following four ways: selective incorporation, syncretic blending, instrumental appropriation and transformative adaptation. These modes involve factors including examination, language policy, material resources and teacher experience. The research finds pedagogical translation is not an